Life Insurance in Russia: Features of Regional Development - Prokopjeva, Evgenia Leonidovna (Economy of Regions, 2015)
Life insurance is the economic tool allowing to accumulate large monetary funds at the level of the country, regions and certain insurers, and also providing growth of a standard of living of citizens and social stability in society. Subject matter of the research is the economic aspects of development of life insurance in regions of Russia. The purpose of the work - to carry out the comparative analysis of functioning of the markets for life insurance in territorial subjects ofthe Russian Federation, to reveal regularities and distinctive features of development of the markets and to define further prospects of branch. Methods of research: analysis, comparison, induction, analogy, mathematical modeling were used. The main results of research: life insurance - a demanded financial product in Moscow, but in regions of Russia demand for it is extremely limited; economic indicators ofthe market have low values and vary on territorial subjects ofthe Russian Federation; statistics of a variation confirm heterogeneity of functioning of the life insurance marketin comparison with the insurance market in general; life insurance volumes in regions of Russia significantly depend on activity of real sector of economy, thus have practically no close interrelation with the income of the population. Collaboration of authorities of all levels and insurance community is necessary for effective development of the life insurance marketin regions. The special attention has to be paid to price policy of insurers, increase of transparency ofthe movement of their financial streams and guarantees of recoverability of means of insurers.